2011
DOI: 10.1111/j.1365-2141.2011.08851.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of a randomized trial in children with Acute Myeloid Leukaemia: Medical Research Council AML12 trial

Abstract: The Medical Research Council Acute Myeloid Leukaemia 12 (MRC AML12) trial (children) addressed the optimal anthracenedione/anthracycline in induction and the optimal number of courses of consolidation chemotherapy. 504 children (<16 years) with AML were randomized between mitoxantrone/cytarabine/etoposide or daunorubicin/cytarabine/ etoposide as induction chemotherapy and 270 entered a second randomization between a total of four or five courses of treatment. Tenyear event-free (EFS) and overall survival (OS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
2
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(185 citation statements)
references
References 28 publications
14
159
2
4
Order By: Relevance
“…Therapy consisted of 5 cycles of intensive chemotherapy based on the UK Medical Research Council 12 study, 10 and patients were randomized to receive or not receive gemtuzumab ozogamicin (GMTZ) at 3 mg/kg per dose once on day 6 during induction I and intensification II. Induction I consisted of cytarabine 100 mg/m 2 per dose intravenously every 12 hours on days 1 through 10; daunorubicin 50 mg/m 2 per dose intravenously on days 1, 3, and 5; and etoposide 100 mg/m 2 per dose intravenously daily on days 1 through 5 (ara-C, daunorubicin, etoposide 10 1 3 1 5).…”
Section: Materials Trial Descriptionmentioning
confidence: 99%
“…Therapy consisted of 5 cycles of intensive chemotherapy based on the UK Medical Research Council 12 study, 10 and patients were randomized to receive or not receive gemtuzumab ozogamicin (GMTZ) at 3 mg/kg per dose once on day 6 during induction I and intensification II. Induction I consisted of cytarabine 100 mg/m 2 per dose intravenously every 12 hours on days 1 through 10; daunorubicin 50 mg/m 2 per dose intravenously on days 1, 3, and 5; and etoposide 100 mg/m 2 per dose intravenously daily on days 1 through 5 (ara-C, daunorubicin, etoposide 10 1 3 1 5).…”
Section: Materials Trial Descriptionmentioning
confidence: 99%
“…Unfortunately, one-third of the patients eventually relapse [1][2][3][4][5][6][7][8]. Over the past years, new therapies have been designed to improve the prognosis in AML including the development of antigen-targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6 Recent results from clinical trials indicate a 1-year overall survival (OS) rate of 60 to 70%. [7][8][9] In children with AML who relapsed post-ASCT and after a second ASCT, it was reported at approximately 30 to 40% by Lee et al 9 In 2013, survival outcomes were reported to be similar between adolescents and children with AML following ASCT. 10 Myeloablative preparative regimen used for ASCT induces profound neutropenia and platelet decrease.…”
Section: Introductionmentioning
confidence: 99%